The Child as a Perfect Simillimum for the Parent - Venema, Janita (Homœopathic Links, 2012)
Children are the ultimate simillimum for their parents and the cured parents the perfect remedy for the children. Homeopathic principles can be used by considering childrenʼs signs and symptoms as an expression of the simillimum they are for their parent(s). Through helping parents to become aware of these healing messages by their children, to translate them and act upon them their children thrive because they themselves do.
Keywords: Children; Parents; Simillimum; PresentChild